Biochemical factors conferring shoot tolerance to oxidative stress in rice grown in low zinc soil - Frei, Michael; Wang, Yunxia; Ismail, Abdelbagi M.; Wissuwa, Matthias (Commonwealth Scientific and Industrial Research Organisation, 2010)
Zinc deficiency reduces rice growth and yield, and this is, in part, due to leaf damage caused by reactive oxygen species (ROS). The aim of this study was to identify biochemical mechanisms conferring tolerance to Zn deficiency-induced oxidative stress. A field experiment and three nutrient solution experiments were conducted with the intolerant genotype IR74 and recombinant inbred lines (RILs) derived from a cross between IR74 and the tolerant landrace Jalmagna. After 2 weeks of growth in low Zn soil, stress symptoms developed in leaves of IR74, but not in the tolerant RIL46. Activity of antioxidant enzymes showed clear treatment effects, but did not explain tolerance of RIL46. On the contrary, the intolerant IR74 showed higher activities of superoxide dismutase (SOD), guaiacol peroxidase (POX), ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR) and glutathione reductase (GR) under Zn deficiency. This contrasted with a constitutively higher level of total and reduced ascorbic acid (AsA) in RIL46. Three further nutrient solution experiments focussed on enzymes and reducing substrates of the ascorbate–glutathione cycle. The first experiment included the highly sensitive RIL76 in addition to the genotypes used in the field trial, to test whether the patterns of antioxidant response observed in the field were specific to the genotypes used. This genotype had similarly low AsA level as IR74, but did not respond to Zn deficiency with an increase in enzyme activity, leading to even more pronounced leaf symptoms. In a second experiment, co-segregation of AsA concentration and Zn deficiency tolerance was confirmed in five genotypes from the IR74/Jalmagna quantitative trait loci (QTL) mapping population. A third experiment was conducted to determine whether the observed patterns of antioxidant response were specific to Zn deficiency or would also apply to oxidative stress caused by iron deficiency. Although high AsA level apparently conferred tolerance under both types of stress, the enzymatic response to iron deficiency differed from that to Zn deficiency. In particular, APX activity showed a decrease instead of an increase under low iron stress. In conclusion, we suggest that a high AsA level is a promising target for developing rice genotypes with tolerance to oxidative stress.